Francesco Di Paola, Andrea Mercurio (2023). Parametric Experiments in Architecture. A Connection Joint Design for Sustainable Structures in Bamboo. Cham: Springer (diségno, 2026)
The book by Francesco Di Paola and Andrea Mercurio belongs to a line of research linked to building practices between tradition and innovation. The authors offer a multidisciplinary perspective that reconciles the most advanced techniques of three-dimensional representation and simulation with the science of materials, construction techniques, and structural mechanics. [read more]